A Novel Biomarker Driving Poor-Prognosis Liver Cancer: Overexpression of the Mitochondrial Calcium Gatekeepers - Chia-Jung Li; Hung-Yu Lin; Chih-Jan Ko; Ji-Ching Lai; Pei-Yi Chu (Biomedicines, 2020)
Several studies have indicated the biological role of mitochondrial Ca2+ uptake in cancer pathophysiology; however, its implications in predicting the prognosis of hepatocellular carcinoma (HCC) are not yet fully understood. Here, we collected tumor specimens and adjacent normal liver tissues from 354 confirmed HCC patients and analyzed the levels of cyclic adenosine monophosphate (cAMP) responsive element binding protein 1 (CREB), mitochondrial calcium uniporter (MCU), mitochondrial calcium uptake 1 and 2 (MICU1, MICU2) using bioinformatics, qRT-PCR, and immunohistochemistry (IHC), and their relationship with clinicopathological characteristics and prognosis. HCC patients with low CREB/MICU1 and high MCU/MICU2 expression exhibited poor survival rate and prognosis in overall survival (OS) and disease-free survival (DFS) analyses. Low CREB/MICU1 and low MICU1 alone indicated poor prognosis in stage I/II and III/IV patients, respectively. In the poor differentiation/undifferentiation group, low expression of MICU1 indicated poor clinical outcomes. Low CREB/MICU1 expression suggested poor outcomes in patients with or without hepatitis B virus (HBV) infection and poor prognosis in the HCV infection group. In the non- hepatitis C virus (HCV) infection group, low MCU1 indicated a poor prognosis. Multivariate analysis demonstrated that CREB and MICU1 expression showed prognostic significance. This study demonstrates the prognostic significance of CREB, MCU, MICU1, and MICU2, in predicting HCC outcomes. Low CREB/MICU1 and high MCU/MICU2 in HCC tissues are associated with poor prognosis, thus offering a novel perspective in the clinical management for HCC patients.